Modern Arabic Modern Composition of Auditory Template: An Analytical Study (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This research aims to shed light on the modern Arabic composition of the auditory template, and to identify the most important developments that occurred in the auditory template among Arab authors during the last quarter of the twentieth century and until now, through analyzing a selected group of Arabic auditory works, which we took into account in their selection the differences in time, place, and author. The research concluded with a set of results, the most important of which was the departure of Arab composers from the traditional form of composition in the auditory template, its formula and structure, through the use of melodic harmonies, the expansion of the vocal space, in addition to melodic phrases that depend on tonal and maqam transformation, fast rhythmic forms, and the construction of the stanzas in a manner that is consistent with modern musical composition, which is based on the use of modern techniques in playing Arabic instruments in musical composition.
Keywords: Template; , Auditory; Structural Formula; Musical Composition; Traditional Arabic Music